The Addition of N-Butanol in Ethanol-Isooctane Mixture to Reduce Vapor Pressure of Oxygenated-Gasoline Blend - Rendra Panca Anugraha; Zul Akbar Andi Picunang; Annas Wiguno; Rizky Tetrisyanda; Kuswandi Kuswandi; Gede Wibawa (Indonesian Journal of Chemistry, 2017)
In this work, vapor pressure of binary systems for isooctane + ethanol, isooctane + n-butanol and ethanol + n-butanol and ternary system for isooctane + ethanol + n-butanol were measured in the temperature range from 313.15 to 318.15 K using the inclined ebulliometer. The experimental results showed that the existence of n-butanol in isooctane decreases the vapor pressure of mixture, while increasing n-butanol fraction in ternary isooctane-ethanol-n-butanol mixture decreased vapor pressure of mixture. Experimental data for binary systems studied were correlated with Wilson, NRTL and UNIQUAC models with average relative deviation (ARD) of 3.5%. The optimized binary parameter pairs obtained in this work were used to estimate the ternary system. The Wilson model gave the best performance for estimation of ternary system with ARD of 5.4%. All systems studied showed non-ideal solution with positive deviation from Raoult’s law.